PENGEMBANGAN PERANGKAT PEMBELAJARAN BIOLOGI BERORIENTASI PENGEMBANGAN KECERDASAN MAJEMUK SISWA PADA KONSEP SEL KELAS XI SMA - Vidya Chaerunnisa; Siti Gia Syauqiyah; Bambang Ekanara (Biodidaktika : Jurnal Biologi dan Pembelajarannya, 2017)
This study aimed to determine the feasibility of the development of student’s multiple intelligence-oriented learning instrument on the cells concept in grade XI senior high school. Research and Development (R & D) method was conducted in this research. This research was developed four components in the cell concept learning instrument that included syllabus, lesson plan, student’s worksheet, and assessment instrument. From the four components were obtained an average score of 93.76% with a decent category. The time limited test was conducted in July-August 2016, at SMAN 4 Kota Serang and SMA Prisma Sanjaya Kota Serang. Based on students' responses as a user, it was obtained the value of 79.78% with a fair category. Based on the results of expert test and limited test scale, the learning instrument development of multiple intelligences learning-oriented can be applied for the learning process in the cell concept for grade XI in senior high school.